The Effect Of Using Word Cards Media On The Beginning Reading Skills Of Second Grade Students At Elementary School 48 Garutu Enrekang Districts - Nining Anggreini; Rohana Rohana; Amir Pada (International Journal of Elementary School Teacher, 2021)
This research is a quantitative approach with the type of pre-experiment research which aims to determine (1) The description of the use of word card media on the early reading skills of grade II students of SDN 48 Garutu, Enrekang District, (2) The description of the early reading skills of grade II students of SDN 48 Garutu, Enrekang District, and (3) The effect of using word card media on the early reading skills of grade II students of SDN 48 Garutu, Enrekang District. The independent variable in this study is the application of the use of word card media, while the dependent variable is students' early reading skills. The population in this study were all grade II students of SDN 48 Garutu, namely 25 people, as well as the sample, namely all grade II SDN 48 Garutu, namely 25 people with the sampling technique, namely saturated sample. The results of the research conducted can be concluded that (1) The description of the use of word card media on the early reading skills of grade II students of SDN 48 Garutu, Enrekang District took place effectively because the percentage category for each meeting increased. (2) The description of the early reading skills of grade II SDN 48 Garutu Enrekang District has increased. This is evidenced by the posttest scores of students in the high category after being given treatment while the pretest scores were in the medium category before treatment. (3) Data on the results of the study were obtained by giving tests of students' early reading skills in the form of pre tests and post tests. Based on the results of inferential statistical analysis, the Sig. (2-tailed) from the results of the Paired Sample Test of 0.000, this value is smaller than α = 0.05. It can be concluded that the use of word card media has a significant effect on the early reading skills of grade II students of SDN 48 Garutu, Enrekang Regency.